THE INFLUENCE OF LEADERSHIP STYLE AND JOB SATISFACTION ON WORK LOYALTY AT CV. HARCO NENCY - Jalukhu, Rice Darlina; Yunita, Mella; Pakpahan, Evelina (International Journal Multidisciplinary (IJMI), 2024)
Objective: This study aims to analyze the partial influence of leadership style on job loyalty, examine the partial impact of job satisfaction on job loyalty, and investigate the combined effect of leadership style and job satisfaction on job loyalty at CV. Harco Nency. Methods: This quantitative research involves 50 employees of CV. Harco Nency, using multiple regression analysis, t-tests, determination coefficient (R²), and F-tests to evaluate the relationships between the independent variables (leadership style and job satisfaction) and the dependent variable (job loyalty). Results: Findings reveal that leadership style significantly affects job loyalty, evidenced by a significance level of 0.000 < 0.005. Job satisfaction also has a significant positive impact on job loyalty, with a significance level of 0.000 < 0.005. Furthermore, leadership style and job satisfaction together significantly influence job loyalty, confirmed by an F-value of 65.592 with a significance of 0.000 < 0.005. Novelty: This study provides insights into the importance of leadership and job satisfaction in enhancing employee loyalty. It highlights the role of other influential factors such as motivation and work enthusiasm, offering a basis for further research on employee loyalty dynamics.